Blockbuster immersive experiences as a product of culture industry - Moraes, Isabella (Revista do Colóquio, 2025)
This paper analyzes immersive blockbuster experiences and the fine line between them as cultural products and consumer products of the cultural industry. The research adopts a qualitative approach based on bibliographic analysis. The results indicate that immersive blockbuster experiences of a commercial nature can be instruments of alienation if the communication system and immersive elements are misused. It concludes that one must critically consider the interests behind productions of this type and how they affect Museology, with the solution residing in the socialization of art and emancipatory museum education.